2015
DOI: 10.3906/biy-1501-28
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of heme oxygenase 1 in Brassica juncea (L.) Czern.(Indian mustard) under salt stress

Abstract: IntroductionAbiotic stress is a global agricultural issue that limits plant growth and yield. Amongst abiotic stresses, salt stress leads to significant crop losses worldwide (Greenway and Munns, 1980). Although natural salts are present in soil, their increased concentration affects plant growth adversely. Rao et al. (2008) reported that salinity affects about 932 million hectares of land globally. In plant cells under salt stress, Na + and Clions accumulate in cytoplasm and lower the external water potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…Previous reports demonstrated that HO 1 plays an imperative role in antioxidant protection towards various abiotic stresses (Balestrasse et al 2005;Yannarelli et al 2006;Verma et al 2015;Santa-Cruz et al 2017;Mahawar et al 2018a). Zilli et al (2009) verified HO 1 stimulation under salinity stress in Glycine max leaves.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous reports demonstrated that HO 1 plays an imperative role in antioxidant protection towards various abiotic stresses (Balestrasse et al 2005;Yannarelli et al 2006;Verma et al 2015;Santa-Cruz et al 2017;Mahawar et al 2018a). Zilli et al (2009) verified HO 1 stimulation under salinity stress in Glycine max leaves.…”
Section: Discussionmentioning
confidence: 65%
“…Tolerance index quantify the inhibitory effect of NaCl on the physiology of plant. The progressive increase in tolerance index at 75 mM concentration signifies the greater tolerance of crop towards NaCl at this concentration which is probably due to the increase activity of antioxidants including HO 1 at 75 mM (Verma et al 2015;Huang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…reducing, metal chelating, lipid reducing and free radical scavenging activities [24,[28][29][30]. These also possess antioxidant enzyme activities as these have been found to enhance the activities of some antioxidant enzymes including glutathione peroxidase, superoxide dismutase, catalase, heme oxygenase and ascorbate peroxidase [21,[31][32][33] ( Table 6). B. oleracea plants have been studied most for their antioxidant activities among the Brassica species and found to possess strong antioxidant potential in terms of reducing power and free radical scavenging capacity.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…In fact, the United Nation Environment Program estimated that approx 20% of irrigated agriculture land in the world is affected by soil salinity (Hasanuzzaman et al 2018). Salinity stress influences various physiological and metabolic pathways of the plant which mainly depends on concentration and duration of stress that eventually leads to a diminution in crop production (Verma et al 2015;Khator and Shekhawat 2019;Khator et al 2020). In plant soil, NaCl is the most prevalent and soluble salt and its elevated concentration incite two principal effects on plant; osmotic stress and ion toxicity.…”
Section: Introductionmentioning
confidence: 99%